PENGARUH TEKANAN STAKEHOLDER TERHADAP TRANSPARANSI LAPORAN KEBERLANJUTAN PERUSAHAAN-PERUSAHAAN DI INDONESIA - Arum Hamudiana; Tarmizi Achmad (Diponegoro Journal of Accounting, 2017)
This study aims to empirically examine the effect of stakeholder pressure on transparency of Indonesian companies’s sustainability report. As a part of CSR communication strategy, each company determines the required level of transparency, which depends on the pressure of specific stakeholders in the industry.The population of this study are firms in Indonesia which published sustainability report within the evaluation period of 2012-2015. Based on purposive sampling method, this study use 91 companies as the samples. The independent variable in this study are environmentally sensitive industry, consumer proximity industry, investor-oriented industry and employee-oriented industry which measured using dummy variables. The dependent variable